1963
DOI: 10.1099/00221287-32-2-277
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interferon in Persistent Infection with Foot-and-Mouth Disease Virus

Abstract: SUMMARYCalf kidney cell cultures persistently infected with foot-and-mouth disease virus (FMDV) resist challenge with related and unrelated viruses. Attachment of challenge virus to persistently infected cells is not impaired. A challenge with viral ribonucleic acid (RNA) will not overcome the resistance of persistently infected cells. The initiation of persistence is correlated with the amount of interferon produced in the cells. It is concluded that interferon plays a major role in initiation and maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1965
1965
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Several persistent infections of tissue cultures are thought to be caused by the interferon system, although only a few definitive studies have been reported. Interferon has been detected at very early and at advanced stages of persistent infection of mouse L cells with Newcastle disease virus (122)(123)(124), human amnion and KB cells with poliovirus (125), calf kidney cells with the WS strain of influenza virus and with foot-and-mouth disease virus (126,127), KB cells with parainfluenza type 3 virus (128), mouse embryo cells with vaccinia virus (50), human amnion and mouse L cells with tick-borne encephalitis virus (53,129), mouse 23 P cells with polyoma virus and with herpes simplex virus (90), and monkey cells with rubella virus (130). Similar results have been observed during the early period of infection of mice with lactic dehydrogenase virus (32).…”
Section: Infectionsmentioning
confidence: 99%
“…Several persistent infections of tissue cultures are thought to be caused by the interferon system, although only a few definitive studies have been reported. Interferon has been detected at very early and at advanced stages of persistent infection of mouse L cells with Newcastle disease virus (122)(123)(124), human amnion and KB cells with poliovirus (125), calf kidney cells with the WS strain of influenza virus and with foot-and-mouth disease virus (126,127), KB cells with parainfluenza type 3 virus (128), mouse embryo cells with vaccinia virus (50), human amnion and mouse L cells with tick-borne encephalitis virus (53,129), mouse 23 P cells with polyoma virus and with herpes simplex virus (90), and monkey cells with rubella virus (130). Similar results have been observed during the early period of infection of mice with lactic dehydrogenase virus (32).…”
Section: Infectionsmentioning
confidence: 99%
“…P~IILIPSO~ and DINTEI~ (14) reported the presence of detectable interferon 4 days after establishment of FMDV persistent calf kidney cell cultures, but the interferon titers were too low to be detected after 10 days. The failure to detect interferon may be due to several possibilities: 1) the interferon Present might be bound intracellularly as suggested by HENLE et al (9) for myxoviruses or 2) the test system for interferon may not be sensitive enough to detect minute amounts of interferon.…”
Section: Discussionmentioning
confidence: 95%
“…The initiation of persistence of FMD virus has been correlated with the production of interferon in cells [45], possibly due to an alteration of the cells. This observation is supported by recent experimental evidence that the FMD virus persistently infected cell phenotype is altered significantly from the parental strain [46].…”
Section: Viral Mechanismsmentioning
confidence: 99%